Three new species of Alburnoides from the southern Black Sea basin (Teleostei: Cyprinidae) - Turan, Davut; Kaya, Cüneyt; Bayçelebi̇, Esra; Bektaş, Yusuf; Ekmekçi̇, F. Güler (Zootaxa, 2017)
Three new Alburnoides species are described from the southern Black Sea basin. Alburnoides kurui, new species, from the Yeşilırmak drainage, is distinguished from other species of Alburnoides in the southern Black Sea basin, the Marmara basin and the Anatolian Aegean basin by having a scaleless keel between the posterior pelvic fin base and the anus or with rarely 1 scale covering the anterior part of the keel; 50–59 total lateral-line scales; 13½–15½ branched anal-fin rays and 7–9 gill rakers. Alburnoides freyhofi, new species, from the Kızılırmak drainage, is distinguished by having a scaleless keel between the posterior pelvic fin base and the anus, 44–53 total lateral-line scales; 14½–16½ branched anal-fin rays and 5–7 gill rakers. Alburnoides kosswigi, new species, from the Sakarya drainage, is distinguished by having a scaleless keel between the posterior pelvic fin base and the anus or rarely with 1–3 scales covering the anterior part of the keel; 43–57 total lateral-line scales; 11½–13 (14)½ branched anal–fin rays and 5–7 gill rakers.